The Dynamics of Phytoplankton Abundance Lake Bunter Pangkalan Baru Village Siak Hulu Sub District Kampar District Riau Province - Muhammad Edom Rifai; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTResearch onthe dynamics of phytoplankton abundance was conducted in July-August 2019 at Lake Bunter Pangkalan Baru village. A study aims to know the dynamics of phytoplankton abundance either spatiallyand temporally. There were 3 stations namely station 1 (inlet area), station 2 (in the middle of the lake) and station 3 (in the end of the lake). In each stations, there were 2 sampling point, in the surface and 2 Secchi depth. Sampling was done 4 times, once/week. Water quality parameters measured were temperature, pH, transparency, dissolved oxygen, free carbon dioxide, nitrate, phosphate. Result shown that temperature 29-32oC, transparency 81-90 cm, pH 5, DO 3.42-8.22 mg/L, CO2 3.99-15.98 mg/L, nitrate 0.022-0.089 mg/L, phosphate 0.014-0.049 mg/L. Phytoplankton abundance at the surface range 317,746-411,070cell/L, and 2 Secchi depth range 284,416-311,080cell/L. Temporal dynamics of phytoplankton abundance was influenced by timewhile spatial dynamics of phytoplankton abundance based on stations or depth. The dynamics of phytoplankton abundance, either spatially and temporally was influenced by water quality such as transparency, nitrate and phosphate.Keywords:Temporal, Spatial, Water Quality, Depth